The Early Mediaeval manorial estate of Gars/Thunau, Lower Austria: An enclave of endemic tuberculosis?. (June 2015) - Teschler-Nicola, Maria; Novotny, Friederike; Spannagl-Steiner, Michaela; Stadler, Peter; Prohaska, Thomas; Irrgeher, Johanna; Zitek, Andreas; Däubl, Barbara; Haring, Elisabeth; Rumpelmayr, Kerstin; Wild, Eva Maria
Summary: In recent decades, an increasing number of studies have aimed to shed light on the origin and spread of tuberculosis in past human populations. Here we present the results of a systematic palaeodemographic and palaeopathological survey of the Early Mediaeval population of Gars/Thunau (Lower Austria), which – at this stage – includes 373 individuals recovered at two archaeological sub-sites: a fortified settlement (including a necropolis) at the top of a hill – probably reserved for social and military elites; and a large riverine settlement at the foot of the hill, a so-called 'suburbium', where burials and an area of 'industrial' character were discovered. We recorded a great number of pathological alterations and a variety of 'classical' features of tuberculosis, such as vertebral destructions (Pott's disease) and joint destructions, and other pathological (unspecific) features probably linked with Mycobacterium tuberculosis infection (e.g. new bone formation at the inner surface of the ribs, endocranial alterations in the form of 'pits', and new bone formation at the cranial base). We hypothesize that the two contemporaneous (∼900–1000 AD) populations of Gars/Thunau differed not only in their social affiliation/condition, but also in the type and frequencies of their population-density-related infectious diseases (in particular tuberculosis). Moreover, we investigated the molecular genetic evidence of the causative organism in a few selected immatures exhibiting pathological changes at the inner wall of the cranium and discuss these findings in regard to the macroscopic features observed. Finally, we analysed carbon and nitrogen stable isotopes of both populations and strontium isotope ratios of the hill-top inhabitants in order to reconstruct certain aspects of diet and mobility to test our hypothesis concerning the specific social and/or military character of the site.